Statistical modeling of the waste utilization value by multiple regression and historical response surface methods - Caldona, Eugene B. (2008)
The waste utilization value (WUV), formulated by W. I. Jose is a a concept developed to evaluate the economic value of wastes and is the value of a waste in monetary unit mass (Pesos/kg). In 1992, Tio forst proposed a classification scheme for the waste utilization value (WUV) using Discriminant Analysis which was applied generally to different types of wastes using very general factors. This study aims to model the WUV of particular types of waste material, namely metal wastes and nonmetal wastes. Multiple Regression and Historical Response Surface Methods (RSM) are used to formulate a model for positive waste utilization values of particular types of waste materials, namely metal and nonmetal wastes. A total of sixteen (16) solid wastes was studied and surveyed in eighty-five (85) junk shops around cities in Metro Manila. Out of these sixteen (16) wastes, twelve (12) were considered for study due to completeness and sufficiency of data obtained. The wastes were grouped as metal or nonmetal wast. Nine (9) factors were used and measured for metal wastes: Tensile Strength, Weldability, Thermal Conductivity, Corrosion Resistance, Hardness, Availability, Handling, Cost and Profit; while eight (8) factors for nonmetal wastes: Availability, Separation, Handling, Product, Demand, Cost, technology and Profit. Model statistics and analysis showed that tensile, weldability, thermal conductivity, hardness and cost are the factors that best determine the selling and buying price, as well as the WUV of a metal waste. For nonmetal wastes, the factors that affect their buying and selling price and the WUV are availability, handling, product, demand, cost, and technological plus a two-factor interaction namely, availability and handlinh particularly in the WUV model. Based on the major contributing factors which are hardness, weldability and cost, an ideal waste metal should be hard and have excellent weldability, and should contain expensive elements; while a nonmetal waste, based on its major contributing factors which are Availability, Cost, Demand and Handling, should be in-demand for recycling purposes, should contain expensive substances and limited mineral resources and should be of high density - so the waste may not look bulky when it comes to both storage and transportation.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Waste (Economics) -- Statistical methods; Regression analysis; Refuse and refuse disposal -- Philippines -- Manila Metropolitan Area